Exploring Communicative Language Teaching to Investigate English Communication Willingness in EFL Learners’ Classroom - Aldha Williyan; Eka Apriani; Sirniawati Sirniawati; Utami Rosalina (STAI Hubbulwathan Duri, 2023)
Being Willing to Communicate (WTC) in English is significant since communicating in another language is considered to be a crucial part of learning a foreign language. Without it, the students only learn English in a passive way. This study, therefore, aims to explore the Communicative Language Teaching (CLT) to investigate the Willingness to Communicate (WTC) in English of EFL learners. This research uses mixed methods, especially Embedded Design, to explore CLT and investigate WTC in English of EFL learners. Qualitative analysis begins this research through observation and interviews. The results of both are then strengthened by the results of quantitative analysis through the questionnaire. It was found that there were various communicative activities implemented by the teacher. Those are effectively conducted by the teacher to promote communicative language teaching in the classroom. Another finding is that there are six WTC patterns, and the pattern of voluntary participation in class activities has the highest percentage of occurrences. The conclusion that can be drawn from this research is that the willingness to communicate (WTC) in English for EFL learners is regarded as high or very willing.